2007
DOI: 10.1002/jsfa.3019
|View full text |Cite
|
Sign up to set email alerts
|

Boysenberry and blackcurrant drinks increased the plasma antioxidant capacity in an elderly population but had little effect on other markers of oxidative stress

Abstract: BACKGROUND: The consumption of fruit and vegetables promotes good health by protecting against various degenerative diseases. Even though the constituents responsible are not known, some evidence indicates that the antioxidant properties of fruit and vegetable phytochemicals are responsible. Previous studies have shown that blackcurrant and Boysenberry reduce oxidative stress using in vitro cell systems. The aim of this study was to determine if blackcurrant or Boysenberry drinks could improve measures of oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 50 publications
2
14
0
Order By: Relevance
“…However, an antioxidant effect was not observed in our sugar placebo group supporting the antioxidant action of the anthocyanins of the BC extract. Similar results have been observed in human feeding trials where the anthocyanins content in plant (13) and fruit (35,36) extracts increased measures of plasma antioxidant capacity, while a sugar placebo had no detectable action. These findings, in combination with the high amount of anthocyanins detected within in the commercial BC extract, leads us to conclude that anthocyanins acted as effective antioxidants in reducing the oxidative stress induced by the 30-min row.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…However, an antioxidant effect was not observed in our sugar placebo group supporting the antioxidant action of the anthocyanins of the BC extract. Similar results have been observed in human feeding trials where the anthocyanins content in plant (13) and fruit (35,36) extracts increased measures of plasma antioxidant capacity, while a sugar placebo had no detectable action. These findings, in combination with the high amount of anthocyanins detected within in the commercial BC extract, leads us to conclude that anthocyanins acted as effective antioxidants in reducing the oxidative stress induced by the 30-min row.…”
Section: Discussionsupporting
confidence: 81%
“…It is also possible that long-term consumption of these compounds may activate adaptive antioxidant and immune modulatory mechanisms. Indeed, consumption of berryfruit juices over several weeks significantly increased plasma antioxidant capacity in elderly individuals and modulated immune responsiveness (35,38). We detected no change in exercise-induced indices in the placebo groups during our 3-wk crossover study, and hence, while the participant's food diaries revealed some consumption of foods that contain anthocyanins as part of their daily nutrition, effects of this consumption was of no significance.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Another study was carried out in subjects with preestablished endogenous oxidative stress derived from smoking [33] . Moreover, in several studies [22,23,[33][34][35] , the effects of dietary antioxidants were enhanced in subjects under conditions of oxidative stress compared with healthy people with a well-balanced redox status, in whom the detection of antioxidant status variations is more problematic. Accordingly, 750 ml of cranberry juice/day consumed by 20 healthy female volunteers for 2 weeks did not modify plasma antioxidant capacity or the activity of SOD, catalase and glutathione peroxidase in erythrocytes -and these observations have been attributed to the use of nutritional doses instead of pharmacological doses, and also to the lack of endogenous oxidative stress in healthy volunteers [24] .…”
Section: Antioxidant Capacitymentioning
confidence: 99%